2022
DOI: 10.1136/bmjopen-2021-060223
|View full text |Cite
|
Sign up to set email alerts
|

What is known from the existing literature about self-management of pessaries for pelvic organ prolapse? A scoping review

Abstract: ObjectivesPelvic organ prolapse can be managed with a pessary. However, regular follow-up may deter women due to the inconvenience of frequent appointments, as well as preventing autonomous decision making. Pessary self-management may be a solution to these issues. However, there remains a number of uncertainties regarding pessary self-management. This scoping review aims to map available evidence about pessary self-management to identify knowledge gaps providing the basis for future research.DesignScoping rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
(199 reference statements)
0
1
0
Order By: Relevance
“…Our findings contrast with those of another Canadian study that found that most women preferred regular appointments with health care providers to the option of self-care [ 9 ]. Storey et al [ 9 ] identified psychological comfort with touching oneself as a factor in choice for provider-led care and hypothesized that this might be related to generational differences and patient age [ 10 ]. Our study, completed 13 years later, included patients with a similar median age but noted a much higher acceptability of self-care.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings contrast with those of another Canadian study that found that most women preferred regular appointments with health care providers to the option of self-care [ 9 ]. Storey et al [ 9 ] identified psychological comfort with touching oneself as a factor in choice for provider-led care and hypothesized that this might be related to generational differences and patient age [ 10 ]. Our study, completed 13 years later, included patients with a similar median age but noted a much higher acceptability of self-care.…”
Section: Discussionmentioning
confidence: 99%